Autobiographical memory in Parkinson's disease: A retrieval deficit. Issue 2 (21st March 2013) - Souchay, Celine; Smith, Sarah Jane
Abstract : This study examined the effects of providing cues to facilitate autobiographical memory retrieval in Parkinson's disease. Previous findings have shown that individuals with Parkinson's disease retrieve fewer specific autobiographical memories than older adult controls. These findings are clinically significant since the quality of autobiographical memory is linked to identity and sense of self. In the current study, 16 older adults with Parkinson's disease without dementia and 16 matched older adult controls were given 3 min in which to recall autobiographical memories associated with five different time periods and to give each memory a short title. Participants were later asked to retrieve the memories in three phases: firstly in a free recall phase; secondly in response to general cues (time periods) and finally in response to specific cues (the short titles previously given). The number of memories and the quality of the memory (general or specific) was recorded in each condition. Compared with matched older adult controls, the Parkinson's disease group was impaired in retrieving the memories that they had previously given in the free recall phase and in response to general cues. The performance of the group with Parkinson's disease was only equivalent to the older adults when they retrieved memories in response to self‐generated cues. The findings are discussed in relation to theories of autobiographical memory and the neuropsychology of Parkinson's disease.